Are Family Physical Activity Habits Passed on to Their Children? - Zovko, Vinko; Djuric, Sasa; Sember, Vedrana; Jurak, Gregor (Frontiers in Psychology, 2021)
Studies of the familial association of physical activity (PA) and sedentary behaviour (SB) have increased in recent years. However, there is a lack of studies that have objectively examined the correlates between parents, grandparents, and childrens’ PA. Therefore, the purpose of this study was to measure PA using accelerometers to determine the extent to which PA and SB correlate among parents, grandparents, and children. A sample of 169 children between 11-14 years (77 boys and 97 girls), 225 parents (98 males and 127 females) and 52 grandparents (16 males and 36 females) were recruited for the current study. Accelerometers RM42 (UKK Terveyspalvelut Oy, Tampere, Finland) were used to determine PA levels of children, parents and grandparents. Epoch was set to 1 second. Mothers' moderate-to-vigorous PA (MVPA) was associated with children's MVPA (p <0.05). After adjusting for age, BMI (child), and educational status, the results remain the same. Results of linear regression analyses for boys' sedentary time showed that fathers' sedentary time was significantly associated with boys (p < 0.01), but not with girls. The association of grandmothers' and grandfathers' MVPA activity with that of children showed that grandparents' MVPA, when adjusted for age, BMI, and educational status, was not a significant predictor (p > 0.05) of children's MVPA (total sample). In contrast, grandfathers' sedentary behaviour was a significant predictor (β = 0.269; p < 0.05) of children's sedentary behaviour (total sample). The results of the current study suggest that parental involvement in PA, particularly by mothers, is important for children's PA and, accordingly, healthy outcomes.